Are people who already cycle and walk more responsive to an active travel intervention?. (September 2018) - Keall, Michael; Chapman, Ralph; Shaw, Caroline; Abrahamse, Wokje; Howden-Chapman, Philippa
Abstract: Introduction: Cycling and walking are transport modes that have potential public health and environmental benefits. Various programmes and interventions have been developed and evaluated that aim to increase active travel levels, including the Model Communities Programme in New Zealand, which increased active trip rates by about 30% relative to control areas. Although health benefits are greater when people with low levels of physical activity increase active travel rates, behaviour change of this group has rarely been studied. Objective: This study aimed to see whether people with low baseline levels of walking and cycling were more or less likely than people with higher baseline levels of walking and cycling to shift from motorised to active travel modes in response to an intervention. Methods: Statistical models were fitted to data from face-to-face surveys that collected travel behaviour and physical activity levels. These surveys were conducted with a cohort of respondents annually over a period starting from the base year of the intervention and spanning the following two years. Findings: Compared to similar people in matched control areas, people already reporting some physical activity in terms of walking and cycling had 24 times (95%CI 2 to 356) the odds of increasing active travel mode share over the course of the study compared to those who did not report any cycling or walking at baseline. Conclusions: To convey maximum benefit to population health, interventions need to consider physically inactive people in particular and encourage active travel amongst this group. The Model Communities programme does not appear to have achieved this, despite important increases in population average active travel levels overall. Highlights: The Model Communities programme increased active travel by around 30% The effects for subgroups of the population needed to be studied We looked at the odds of mode shift in relation to baseline PA levels The intervention had a much larger effect on people who were already active